2002
DOI: 10.1124/jpet.102.036533
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Metabolism of Bufuralol Racemate and Enantiomers in Human Liver Microsomes

Abstract: A new HPLC method was developed using a chiral column to efficiently separate four 1ЈЈ-hydroxybufuralol (1ЈЈ-OH-BF) diastereomers that are major metabolites of bufuralol (BF). Employing this method, we examined diastereomer selectivity in the formation of 1ЈЈ-OH-BF from BF racemate or enantiomers in four individual samples of human liver microsomes. Three different human liver microsomes showed a selectivity of 1ЈЈR-OH Ͻ 1ЈЈS-OH for BF enantiomers, which was similar to that of recombinant CYP2D6 expressed in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 12 publications
4
20
0
Order By: Relevance
“…Interestingly, the authors found that three of the four individual samples of liver microsomes showed selectivity of formation of 1′-R-hydroxybufarolol < 1′-S-hydroxybufarolol; this was in agreement with the results from the purified recombinant CYP2D6 isozyme (Narimatsu et al, 2002). However, the fourth individual sample of liver microsome showed an opposite enantioselectivity in the formation of the metabolite (i.e.…”
Section: Screen(s) For Cyp Isozymes -Differential Activity In Vitrosupporting
confidence: 75%
See 3 more Smart Citations
“…Interestingly, the authors found that three of the four individual samples of liver microsomes showed selectivity of formation of 1′-R-hydroxybufarolol < 1′-S-hydroxybufarolol; this was in agreement with the results from the purified recombinant CYP2D6 isozyme (Narimatsu et al, 2002). However, the fourth individual sample of liver microsome showed an opposite enantioselectivity in the formation of the metabolite (i.e.…”
Section: Screen(s) For Cyp Isozymes -Differential Activity In Vitrosupporting
confidence: 75%
“…Regardless of the mephenytoin phenotype, the carvedilol pharmacokinetics in patients was affected by the CYP2D6 phenotype only (Zhou and Wood, 1995). More recently, Narimatsu et al (2002) observed a reverse diastereoselectivity in the hydroxylation of bufarolol to 1″-hydroxy bufarolol metabolite between CYP2C19 and CYP2D6. Another recent example involving fluoxetine and norfluoxetine substrates confirmed lack of correlation between CYP2D6 and CYP2C19 genotypes when individual enantiomers were considered for the evaluation (Scordo et al, 2005).…”
Section: Lack Of Overlap Of Cyp2d6 With Cyp2c19 And/or Cyp2c9 Pathwaymentioning
confidence: 94%
See 2 more Smart Citations
“…It has been reported that oxidative metabolism of carvedilol is catalyzed generally by CYP2D6, which also metabolizes a number of other ␤-blockers such as metoprolol, propranolol, and bufuralol (Madani et al, 1999;Johnson et al, 2000;Narimatsu et al, 2002). However, with the exception of propranolol, there are no reports on the human UGT isoforms involved in the glucuronidation of ␤-blockers Li et al, 2001).…”
Section: Discussionmentioning
confidence: 98%